Prostitution and Sex Trafiking - Nikolić, Zlatko (Zbornik Instituta za kriminološka i sociološka istraživanja, 2007)
The wave of expansion of prostitution in our regional surroundings that swept us in the early nineties with the disintegration of the former country and following transition and impoverishment of the nation, got even more complicated with the addition of the people-trading or sex trafficking phenomenon. The development of the phenomenon itself was greatly influenced and initiated by wars in the surroundings, the presence of foreign armies and soldiers in the region, as consumers of such "services" and the development of new transitional routes in the area (to Kosovo and Metohia, Bosnia, etc). That way, the so-called "oldest trade" grew from a relatively insignificant and tolerable socially pathological issue to a disturbing criminal activity that forced us as a state to incriminate and mark sex trafficking as a criminal act punishable by law. Is that just enough, why is prostitution so liable to criminalization and exploitation, and how can we suppress it, is the theme of this article.